Offering Rituals (Sesajen): Synthesis of Religion and Culture from the Perspective of Islamic Religious Groups - Rohman, Abdul; Mintarti, Mintarti; Asyik, Noor (The Faculty of Islamic Theology and Humanities, UIN Walisongo Semarang, Indonesia, 2023)
This research examines the community's offering rituals to honor gods, ancestral spirits, and guardian spirits of sacred places. This ritual caused controversy among Muslims because it contained elements of shirk. This research aims to seek a synthesis of this controversy. This research uses a qualitative descriptive method approach with an ethnographic type. Data collection was carried out through observation and interviews. Data analysis uses interactive methods. The research results show that offering rituals can be synthesized from a religious and cultural perspective with the following conditions: 1) offering rituals are positioned as cultural events, not as offerings as in religion; 2) the meaning of the offering ritual is thanksgiving which is consumed by the community, not left to be eaten by spirits or ancestral spirits because it would be wasteful; 3) the intention of the offering ritual is only for Allah alone and is not mixed or added with other names. As in religion, the intention of sacrifice is for Allah alone, but the object (sacrificial animal) is for humans.